Effects of Bifidobacterium Pseudocatenulatum G4 on Clostridium Scindens and Clostridium Hiranonis - Rasti, Babak (2009)
The purpose of this study was to investigate the deoxycholic acid (DCA) reduction by Bifidobacterium pseudocatenulatum G4 at in vitro conditions with the emphasis of its bile salt deconjugation ability and antagonistic activity against 7α-dehydroxylating bacteria. B. pseudocatenulatum G4 showed antagonistic activity against Clostridium scindens and C. hiranonis at colonic pH (5.7, 6.2 and 6.8), with highest activity (4mm inhibition zone) at pH 5.7 against C. hiranonis. Growth rates of B. pseudocatenulatum G4 (time required for the initial absorbance at zero time to increase by 0.3 units), decreased in the presence of 2.0% oxgall compared to absence of oxgall. Effect of B. pseudocatenulatum G4 on pH reduction was measured; B. pseudocatenulatum G4 reduced pH from 6.8 to 3.9 in TPY broth supplemented with 0.1% and pH 3.74 in TPY broth without oxgall (control), compared to pH 5.28 in TPY broth supplemented with 2.0% oxgall. This results showed oxgall exert inhibitory effect on pH reduction by B. pseudocatenulatum G4. Bile salt hydrolase (BSH) activity, which is the measurement of enzyme activity responsible for bile salt deconjugation, was quantified by high pressure liquid chromatography (HPLC) assay. B. pseudocatenulatum G4 gave deconjugation rate (disappearance of conjugated bile acid) in TPY broth supplemented with 0.25 mM (the highest concentration in colon) and 5.0 mM (the highest concentration in small intestine) of all 6 different conjugated bile acids (TCA, GCA, TCDCA, GCDCA, TDCA, and GDCA). Generally B. pseudocatenulatum G4 deconjugated glycoconjugated bile acids in higher amount compare to tauroconjugates. The percentage of deconjugation activity was higher in TPY medium supplemented with 0.25mM bile acids compared to TPY broth with 5.0mM bile acids. On other hand, pH 6.2 was observed as the optimum pH for BSH activity. Full factorial statistical design was used to evaluate the effects of three factors (pH, B. pseudocatenulatum G4 concentrations and Clostridiums) with different levels and interactions between them, on DCA production. Statistical analysis for results of the in vitro experiment showed that total DCA concentration produced by C. scindens and C. hiranonis in the presence of B. pseudocatenulatum G4 and low pH, were lower than the control group with highest pH and in the absence of B. pseudocatenulatum G4.